PENINGKATAN COMPUTATIONAL THINKING MELALUI PELATIHAN PEMROGRAMAN VISUAL DAN ANALISIS LOGIKA ALGORITMA BAGI SISWA KELAS 11 TINGKAT MENENGAH ATAS - Nurcahyono, Sigit; Khaerani A, Afifah (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
The digital era requires high school students to possess critical and systematic problem-solving skills, summarized in computational thinking competencies. However, the uneven penetration of the informatics curriculum causes many 11th-grade students to still face difficulties in understanding abstract algorithmic logic. This Community Service (PkM) activity aims to enhance students' computational thinking skills through block-based visual programming training and algorithmic logic analysis. The implementation method utilizes a Project-Based Learning (PjBL) approach consisting of three main stages: (1) introduction to the pillars of computational thinking (decomposition, pattern recognition, abstraction, and algorithms); (2) implementation of logic through visual programming platforms; and (3) completion of coding challenges. The results of the activity showed a significant increase in students' average logic scores between before and after the training. Students were able to transform abstract logic into systematic visual program structures. This program proves that the visual programming approach is effective in reducing technical barriers (syntax barriers) so that students can focus more on strengthening their reasoning and digital creativity.